2013
DOI: 10.1177/1468798413480516
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thematically related play on engagement in storybook reading in children with hearing loss

Abstract: This study examined whether theme-related play increased subsequent engagement in storybook reading in preschool children with typical hearing and with hearing loss. Method: This study employed a counterbalanced experimental design. In all sessions, participants engaged in free play first and then were read a storybook. In the experimental condition, the play materials matched the theme of the book, and in the control condition it did not. Conditions were presented in random order. Storybooks had language at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The majority of the research in this review focused on social aspects, and cognitive aspects observed in play behaviors of children who are deaf. Only one study focused on literacy development (Pataki, Metz, & Metz, 2014). The absence of research on play and literacy among children who are deaf is unexpected finding because play in ECE has not only been associated with the whole child's development but with the development of literacy skills.…”
Section: Discussion Conclusion and Future Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the research in this review focused on social aspects, and cognitive aspects observed in play behaviors of children who are deaf. Only one study focused on literacy development (Pataki, Metz, & Metz, 2014). The absence of research on play and literacy among children who are deaf is unexpected finding because play in ECE has not only been associated with the whole child's development but with the development of literacy skills.…”
Section: Discussion Conclusion and Future Implicationsmentioning
confidence: 99%
“…Other quantitative studies investigated the relationship between language and play (Casby & McCormack 1985;Lederberg, 1991;Quittner, Cejas, Wang, Niparko, & Barker, 2016;Schirmer, 1989). There was one experimental study (Pataki, Metz, & Metz, 2014) and one longitudinal study (Quittner et al, 2016).…”
Section: Research Designsmentioning
confidence: 99%
See 3 more Smart Citations